Factors Associated With Reintubation in Patients With Chronic Obstructive Pulmonary Disease. Issue 4 (October 2015) - Nantsupawat, Nopakoon; Nantsupawat, Teerapat; Limsuwat, Chok; Sutamtewagul, Grerk; Nugent, Kenneth
Abstract : Background: Acute exacerbations of chronic obstructive pulmonary disease (COPD) increase morbidity, mortality, and health care costs in COPD patients. Patients who require mechanical ventilation and fail extubation often have longer hospital stays and/or increased mortality. Determining predictors to identify patients who might require reintubation could help respiratory care teams manage these patients better. Methods: We retrospectively reviewed data of COPD patients over a 3-year period. Inclusion criteria were patients with acute exacerbations of COPD, age more than 45 years, and patients on mechanical ventilation. Exclusion criteria were ventilated via tracheostomy, unplanned extubation, and reintubation for reasons other than respiratory failure. Results: This study included 88 patients; 61 patients were successfully extubated, 11 patients were extubated and required reintubation, and 16 patients were not extubated during their intensive care unit stay. There were no differences in demographic or clinical characteristics between the patients with successful extubation and failed extubation. Patients with successful extubation were more likely to have a "good cough" assessment and to not receive any sedatives or analgesics in the 24 hours prior to extubation than patients who failed extubation ( P < .05). Multiple variable logistic regression demonstrated that reintubation was significantly associated with sedatives/analgesics given prior to extubation (odds ratio = 8.6; 95% confidence interval, 1.23-60.8). Intensive care unit and hospital lengths of stay, tracheostomy events, and mortality rates were higher in the reintubation group ( P < .001). Conclusion: Sedative and analgesic drug use prior to extubation was associated with more frequent reintubation in patients with acute exacerbations of COPD. This study suggests that the judicious withdrawal of sedatives prior to extubation may reduce reintubations.